Co-Authorship Trends in Philosophy of Education Journals in the US and Canada - Taylor, Rebecca; Lee, Seunghyun; Murphy Brust, Caitlin (Philosophical Inquiry in Education, 2024)
A variety of epistemic practices and norms influence how knowledge and understanding are advanced in academia. Co-authorship practices and norms, the focus of this paper, have implications for the epistemic resources that are brought into individual scholarly works and how the resources are distributed among networks over time. Although co-authorship is widely accepted in social scientific research in education, single authorship has remained predominant in philosophy of education. This paper is part of a project exploring co-authorship practices and norms in philosophy and, in particular, philosophy of education. We aim to develop an empirical understanding of co-authorship trends in four primary philosophy of education journals in the United States and Canada. We examine the frequency of co-authorship in these outlets over the last two decades, the participants in co-authored projects, and the philosophical topics that are being explored through co-authorship. Our findings indicate that these venues are publishing co-authored works with increasing frequency and that most co-authorship is happening among faculty collaborators and among scholars who share common disciplinary backgrounds. The observed increase in the practice of co-authorship in these philosophy of education journals points to the significance of exploring it in greater depth, including giving attention to questions of ethics and epistemology that co-authorship raises, as well as to comparative analyses of trends around the world.